Nonlinear Narratives: Paths of Indirect and Relay Translation - Washbourne, Kelly (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
Following Dollerup’s (2000) classification of indirect and relay translation (here “T2”), this study locates both practices as translation taboos disparaged or tolerated depending upon cultural variables, shows its codification in translation organizations, and traces part of its aura of substandard practice to the doctrine of untranslatability; compiles the main reasons the phenomena have occurred, including extralinguistic factors; outlines some subclasses in a typology of ‘second-hand’ or intermediate translations (factoring in abridgements, adaptations, modernizations, lost originals, pseudotranslations, self-translations, triangulations, and transcreations); proposes ‘translative’ and ‘terminal’ relay, and overt and covert possibilities within retranslation, interlinear translation, plagiarism by translation, and support translation; considers the special case of sacred texts; and weighs new and future directions for study. The key factors of oral intermediation (the role of informants and collaborative translation) and the ‘intuiting’ of source languages without a working knowledge of them are brought into the equation. The work attempts to contribute a descriptive study to an area of research that has attracted visceral rejections of anything but source-to-target direct translation without such studies making allowances for the socio-historical conditions of production surrounding intermediary translation.